Overcoming Aggressive Behavior in Early Childhood with the Puppet Show Theater Method - Ainun Alkaff; Rudi Cahyono (Psycho Holistic, 2022)
The purpose of this research is to know the effectiveness of play therapy with the methods the puppet show the theater to reduce aggressive behavior. early childhood. This research involving a student in kindergarten x who have family problems aggressive behaviour towards her, teacher and parents.This study using a qualitative approach with a method of action reseach. Informant research is based on purposive sampling  Data collection techniques using, method of observation interviews and formal tests; CBCL ( child behavior checklist ) and DDTK (deteksi dini tumbuh kembang anak).The research found that method of the puppet show the theater is effective to reduce aggressive behavior on the subject for several days.These results in terms of the observations of the behavioral changes the subject after the intervention.But, aggressive behavior increased again in the day to 9 and to 10 after the intervention.